Training of basic laparoscopic skills in surgical education - Simutis, Gintaras; Drungilas, Mantas; Petrik, Pavel; Petrik, Eglė; Beiša, Virgilijus; Strupas, Kęstutis (Lietuvos chirurgija, 2013)
Background / objectiveThe study was carried out to evaluate the potential use of laparoscopic simulators to enhance basic laparoscopic skills until proficiency is reached.Materials and methodsThe study participants were divided into two groups according to their experience in laparoscopic procedures: no prior experience (group A; n = 16) and laparoscope navigation experience (group B; n = 16). All the participants performed nineattempts of three basic laparoscopic skill tasks (“Instrument navigation”, “Cutting”, “Clip applying”) on the LapSim® simulator during three sessions within one month. The distribution of practice sessions was standardized by performing three attemptsfor each task per session and no more than one session per week. The assessment of laparoscopic skills was based on the cumulative score for each task measured by the computer system.ResultsTrainees in the group A were younger (22.2 ± 1.3 vs. 26.1 ± 1.3 years, P < 0.001). There were statistically significant differences in cumulative scores for all three tasks after the first five attempts between the two groups (P < 0.001). Comparison of thecumulative scores for the task “Instrument navigation” after the sixth attempt (P = 0.073), for the task “Clip applying” after the seventh attempt (P = 0.287), and for the task “Cutting” after the eighth attempt (P = 0.080) showed no significant differences among the study groups.ConclusionsThe results indicated that a group of trainees with no prior laparoscopic experience acquired the basic laparoscopic skills significantly faster. Proficiency in the laparoscopic basic tasks was achieved within 6–8 repetitions in both groups. These findings suggest that training of practical skills in using laparoscopic simulators should be integrated into medical education much earlier.Key words: surgical education, simulation, laparoscopy, virtual reality simulator, LapSimBazinių laparoskopinių įgūdžių įgijimas studijuojant medicinąTikslasAtlikti tyrimą, siekiant įvertinti kompiuterinių laparoskopinių simuliatorių naudojimą medicinos studijoms mokant pagrindinių laparoskopinių operacijų įgūdžių, kol bus įgyta reikiama patirtis.MetodikaTyrimo dalyviai pagal patirtį buvo suskirstyti į dvi grupes: vienos grupės tiriamieji neturėjo jokios išankstinės laparoskopinių operacijų patirties (A grupė, n=16), o kitos grupės turėjo tik navigacijos laparoskopu patirties (B grupė, n=16). Visi dalyviai pertrejas pratybas su laparoskopiniu virtualiu simuliatoriumi LapSim® atliko trijų pagrindinių laparoskopinių užduočių („Instrumentų navigacija“, „Pjovimas“, „Kabučių uždėjimas“) devynis bandymus. Kiekvieną užsiėmimą atskira užduotis buvo kartojamatris kartus, o užsiėmimas vyko ne dažniau nei kartą per savaitę. Vertintas galutinis užduoties rezultatas. Laparoskopinių operacijų įgūdžiai vertinti kompiuterine sistema pagal išvestinį kaupiamąjį kiekvienos užduoties balą.RezultataiA grupės dalyviai buvo jaunesni (22,2±1,3 vs. 26,1±1,3 metų, p